Human case of gastric infection by a fourth larval stage of Pseudoterranova decipiens (Nematoda, Anisakidae) - Mercado Rubén; Torres Patricio; Maira Jorge (Universidade de São Paulo, 1997)
Only three cases of human infection by anisakid nematodes have been reported in Chile since 1976. In the present case, an anisakid worm, identified as a fourth-stage Pseudoterranova decipiens larva, was removed with a gastroendoscopic biopsy clipper from the stomach of a 45 year-old man from southern Chile. The patient, who presented acute epigastric pain and a continuous sensation of having an empty stomach, reported having eaten smoked fish. The worm was fixed in 70% ethanol and cleaned in lactophenol for morphological study. The morphometric characteristics of the worm are described and drawn. Anisakid larvae in fish flesh can be killed by freezing or cooking.